2020
DOI: 10.5194/nhess-20-3197-2020
|View full text |Cite
|
Sign up to set email alerts
|

A systematic exploration of satellite radar coherence methods for rapid landslide detection

Abstract: Abstract. Emergency responders require information on the distribution of triggered landslides within 2 weeks of an earthquake or storm. Useable satellite radar imagery is acquired within days of any such event worldwide. Recently, several landslide detection methods that use these data have been developed, but testing of these methods has been limited in each case to a single event and satellite sensor. Here we systematically test five methods using ALOS-2 and Sentinel-1 data across four triggering earthquake… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…CC BY 4.0 License. aftermath of major triggering events [Mondini 2017, Adriano et al 2020, Burrows et al, 2020, Jung & Yun 2020. The most widely used technique is to map landslides directly from optical imagery, either from Unmanned Aerial Vehicle (UAV) imagery [Casagli et al 2017, aerial photography [Harp et al 2004] or satellite observations [Casagli et al 2017, Martha et al 2012, Behling et al 2014.…”
Section: Landslide Inventoriesmentioning
confidence: 99%
“…CC BY 4.0 License. aftermath of major triggering events [Mondini 2017, Adriano et al 2020, Burrows et al, 2020, Jung & Yun 2020. The most widely used technique is to map landslides directly from optical imagery, either from Unmanned Aerial Vehicle (UAV) imagery [Casagli et al 2017, aerial photography [Harp et al 2004] or satellite observations [Casagli et al 2017, Martha et al 2012, Behling et al 2014.…”
Section: Landslide Inventoriesmentioning
confidence: 99%
“…The mean slope angle is 10° ± 8° (± 1 standard deviation) with a maximum slope of 84°. This EOI was also previously investigated using SAR change detection methods by Adriano et al, (2020), Burrows et al (2020) and Jung and Yun (2020). These studies showed that both coherence change and backscatter intensity change detection methods work to characterize the landslides, however the backscatter based methods outperform SAR coherence change detection in the vegetated mountains (Jung and Yun, 2020).…”
Section: Earthquake-triggered Landslides Hokkaido Japanmentioning
confidence: 76%
“…In this way, the landslide density heatmap is a proxy for potential landslide occurrence and not a heatmap of observed landslides classified using other methods. Several recent studies have applied a landslide density map approach to identify critically damaged areas, rather than focus on the location of individual landslides (e.g., Bessette-Kirton et al 2019;Burrows et al, 2020;Rosi et al, 2018). Our landslide density heatmaps are similar to these other density maps, however instead of counting individual landslides, we calculate the density of individually detected pixels over a fixed area.…”
Section: Landslide Density Heatmapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentinel-1 ICFs might therefore play a larger role in empirical models based in arid environments than they did here. Sentinel-1 InSAR coherence has been used to map erosion in arid environments (Cabré et al, 2020), indicating that it could also be applied to landslides. However, it is also more difficult to derive landslide inventories from optical satellite images in less vegetated areas.…”
Section: Possible Application In Other Settingsmentioning
confidence: 99%